Value of Indirect Hemagglutination and Coagglutination Tests for Serotyping Haemophilus parasuis - Del Río, M. L. (American Society for Microbiology, 2003)
An indirect hemagglutination test (IHA) and a coagglutination test (CA) were evaluated using saline, boiled, and autoclaved extracts for serotyping Haemophilus parasuis. CA showed several cross-reactions, whereas IHA gave rise to specific reactions, with minor exceptions. IHA was further compared with the immunodiffusion test (the “gold standard”) for the serotyping of 67 field isolates. As a conclusion, IHA is recommended as a useful method for sensitive and specific serotyping of H. parasuis.